IS THERE ANY DIFFERENCE BETWEEN SALES FORCE AND SALES MANAGER PERCEPTIONS ON THE SALES FORCE AUTOMATION IMPLEMENTATION? - Dwidienawati, Diena; Abdinagoro, Sri Bramantoro; Gandasari, Dyah (International Journal of Psychosocial Rehabilitation, 2020)
SFA has been proven to be related to performance and productivity. SFA implementation required huge investment and study showed that failure rates of SFA implementation is as high as 40-80%. Regardless the fact, studies on SFA are limited. In the last 5 years, there are only 44 SFA studies published in Science Direct. Differences between managers and sales force in their perceptions of a new technology can affect the acceptance and implementation of that technology. The difference perception can undermine the issue face by the sales force. Different perception between Sales Force and managers will risk the success of SFA implementation. This study aims to see whether there is difference perception between sales force and sales manager on how SFA helps their daily works. Quantitative study was conducted in one multinational pharma company in Indonesia. Structured questionnaires with 5 Likert’s scale were distributed to 50 sales force and 20 managers. The difference between two group was analyzed using two-sample T-test. The result showed that there was difference perception between sales force and managers on how SFA could help achieving performance, managing sales force, accessing information and planning. However, in-term how SFA help them doing their daily activity such as monitor call, how training and support staff are key, there was no difference between group. This study contributes to the empirical evidence of SFA literature.